Implementasi Penggunaan Aplikasi QuickBook Di Dalam Meningkatkan Efektivitas Manajemen Keuangan Pada Client Di Kantor EF Sinergy Consultant Pajak Surabaya - Lilyana Fransiska Sinaga; Yanda Bara Kusuma (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research will focus on discussing how the implementation of the use of the QuickBooks application used by the EF Sinergy Consultant Surabaya Office in improving the effectiveness of financial management at their clients. Where this application is an application that can assist companies in managing company financial transactions, creating financial reports, and monitoring cash flow more effectively. In addition, this application can also help companies save time and costs incurred in managing their finances. The QuickBooks application is aimed primarily at MSMEs or taxpayers from the middle to lower class. The method used in this research is descriptive qualitative method. Data collection techniques are obtained from direct observation in the field and interviews with one of the relevant sources. Researchers used primary data sources from observations and interviews and used references from journals, the official website of EF Sinergy Consultant Surabaya, and several other supporting websites. The results showed that the implementation of the QuickBooks Application has long been used by EF Sinergy Consultant Tax Surabaya as the right software in providing services to manage client financial reports accurately.